2004
DOI: 10.1212/01.wnl.0000141852.65175.a7
|View full text |Cite
|
Sign up to set email alerts
|

fMRI language task panel improves determination of language dominance

Abstract: A panel of fMRI language paradigms may be more accurate for evaluating partial epilepsy patients than a single task. A panel of tasks reduces the likelihood of nondiagnostic findings, improves interrater reliability, and helps confirm language laterality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
223
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(241 citation statements)
references
References 42 publications
14
223
2
2
Order By: Relevance
“…These and our results confirm the utility of fMRI in presurgical evaluation of patients with pharmacoresistant epilepsy and add to the growing body of evidence that fMRI can be used for presurgical language localization. Some of the more recent studies used a combination of fMRI tasks for evaluation of language functions in patients with epilepsy, and at least one study proposed using fMRI instead of the IAP [33,49]. Furthermore, one fMRI study using the SDTD task in patients with left temporal lobe epilepsy has already shown 100% sensitivity and 73% specificity in predicting significant naming decline after epilepsy surgery when language was lateralized to the left hemisphere, confirming the clinical utility of this fMRI task in presurgical evaluation of epilepsy surgery patients [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These and our results confirm the utility of fMRI in presurgical evaluation of patients with pharmacoresistant epilepsy and add to the growing body of evidence that fMRI can be used for presurgical language localization. Some of the more recent studies used a combination of fMRI tasks for evaluation of language functions in patients with epilepsy, and at least one study proposed using fMRI instead of the IAP [33,49]. Furthermore, one fMRI study using the SDTD task in patients with left temporal lobe epilepsy has already shown 100% sensitivity and 73% specificity in predicting significant naming decline after epilepsy surgery when language was lateralized to the left hemisphere, confirming the clinical utility of this fMRI task in presurgical evaluation of epilepsy surgery patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…Bahn and colleagues reported that language lateralization with IAP and that with fMRI tasks agreed in all patients, but only the results of visual analysis were presented [13]. In contrast to the aforementioned studies, Galliard and colleagues used five different language fMRI tasks to determine language lateralization in 26 predominantly right-handed patients with epilepsy with left hemispheric seizure onset [33]. These authors reported significant agreement between the IAP and language lateralization with a panel of fMRI tasks, and they suggested that the panel may improve designation of language laterality in patients with epilepsy when compared with a single task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have demonstrated prominent activations in left prefrontal areas (45,65-67), with less consistent activations in temporoparietal regions (65). Such data have led some experts to conclude that fMRI may be better suited for localizing expressive language areas within the frontal lobe than receptive language areas within temporal lobe regions ((68,69), but see (70,71)). Overall, results suggest approximately 90% concordance between fMRI and IAP lateralization in patients with TLE, with less impressive results in patients with extratemporal epilepsy (72).…”
Section: Fmrimentioning
confidence: 99%
“…In addition, there are data demonstrating that fMRI language activations complement electrocortical stimulation findings (73) and predict post-operative naming decline (74). Although no single fMRI task has emerged as superior for language lateralization, there is some evidence that a panel of tasks, including verbal fluency, reading comprehension, and auditory comprehension may provide the most reliable results (70).…”
Section: Fmrimentioning
confidence: 99%